2007
DOI: 10.1071/dn07042
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of pure compounds isolated fromTagetes minutaoil toMeloidogyne incognita

Abstract: Essential oils are natural volatile substances found in a variety of plants. The toxicity of z-β-ocimene and dihydrotagetone (isolated from the oil of Tagetes minuta) to eggs and juveniles of Meloidogyne incognita was investigated in vitro. Tagetes minuta oil at 4%, 3%, 2% and 1% was strongly toxic to eggs and juveniles of M. incognita. Further studies revealed that dihydrotagetone and z-β-ocimene isolated from the oil showed strong nematicidal activity against M. incognita, with dihydrotagetone showing a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…The insecticidal and phytotoxic potential of this terpene has been previously demonstrated [9,13]. On the other hand, dihydrotagetone and (Z)-βocimene showed nematicidal activity against eggs and juveniles of M. incognita [14]. To our knowledge, this is the first report on the nematicidal effect of an essential oil rich in (E)-ocimenone.…”
supporting
confidence: 53%
“…The insecticidal and phytotoxic potential of this terpene has been previously demonstrated [9,13]. On the other hand, dihydrotagetone and (Z)-βocimene showed nematicidal activity against eggs and juveniles of M. incognita [14]. To our knowledge, this is the first report on the nematicidal effect of an essential oil rich in (E)-ocimenone.…”
supporting
confidence: 53%
“…Other typical compounds found in the genus Tagetes such as ( Z )‐tagetone (4.7%), ( E )‐tagetone (2.3%), and spathulenol (1.7%) also appear in high levels. Compounds such as ( Z )‐ β ‐ocimene (1.1%) and dihydrotagetone (0.4%) are present in lower levels; these two compounds were isolated by Adekunle et al . from Tagetes minuta essential oil and were reported to have suitable anthelmintic activities against the root‐knot nematode Meloidogyne incognita .…”
Section: Resultsmentioning
confidence: 99%
“…(E)-Ocimenone, the principal component of Tagetes minuta essential oil, may play a major role in nematicidal activity against M. javanica [45]. Furthermore, another study reported that dihydrotagetone and (Z)-β-ocimene, which are also components of the essential oil of T. minuta, have certain nematicidal activities against M. incognita [46]. The volatile nematicidal component against M. javanica of Eupatorium viscidum has been found to be 6-methyl-5-hepten-2-one [47].…”
Section: Nematicidal Vocs From Asteraceaementioning
confidence: 99%